Evaluation of EAP Programs in Iran: Document Analysis and Expert ‎Perspectives - Abutaleb Iranmehr; Mahmood Atai; Esmat Babaii (Applied Research on English Language, 2018)
This study aimed to examine the policies in the Iranian English for Academic Purposes (EAP) education and the extent to which objectives match the policies and are materialized in practice. To this end, course descriptions in the syllabi for the EAP programs were evaluated through document analysis and triangulated with the experts’ perspectives through interviews to examine the current status of EAP policy-making and practice in Iran. Seven policy areas from Kaplan and Baldauf’s (2005) language-in-education planning were chosen as the framework of the study. Based on document analysis and interviews with the experts, the similarities and discrepancies in micro and macro levels were investigated. The results showed that EAP course descriptions do not include any comments on policy and there were discrepancies in policy and practice due to such factors as lack of communication channel between the EAP stakeholders and policy-makers. Finally, the study revealed that due to deficiencies in both policy and practice and in order to reach an acceptable status, EAP programs are in dire need for reconceptualizing policy-making and practice. The findings of this study have significant implications for EAP policies and practice in the academic system of Iran.